PENDIDIKAN ISLAM ABAD 21 PERSPEKTIF DISIPLINER DAN INTERDISIPLINER - Sitti Chadidjah; Mohamad Erihadian; Asep Saefulmillah (FASTABIQ: JURNAL STUDI ISLAM, 2020)
This research is a study of disciplinary and interdisciplinary research in Islamic education dealing with 21st century learning skills. The problem faced by Islamic education is the adjustment of Islamic education in the era of digitalization and learning in the 21st century with the aim of preparing generations of Muslims who are ready to live in accordance with their times. This study focuses on educational institutions and curriculum. The disciplinary approach is problem solving through a theological and interdisciplinary approach in question: problem solving through allied science including; educational philosophy, psychology, Islamic education. This study uses a qualitative approach with literature study as a basis for data collection. One of the characteristics of qualitative research is to explore issues thoroughly, from various books and journals related to the theme, both from within and outside the country, then analyzed.This paper produces 1) one discourse that the disciplinary and interdisciplinary approach is able to solve the problems faced by Islamic education in the 21st century, 2) the disciplinary and interdisciplinary blend of concepts that are inseparable in solving and dealing with current Islamic education problems.Keywords: disipliner, interdisipliner, islamic education